A CRISPR Screen Using Subtilase Cytotoxin Identifies SLC39A9 as a Glycan-Regulating Factor - Yamaji, Toshiyuki; Hanamatsu, Hisatoshi; Sekizuka, Tsuyoshi; Kuroda, Makoto; Iwasaki, Norimasa; Ohnishi, Makoto; Furukawa, Jun-ichi; Yahiro, Kinnosuke; Hanada, Kentaro (iScience, 2019)
Subtilase cytotoxin (SubAB) is a virulence factor produced by locus of enterocyte effacement-negative Shiga-toxigenic Escherichia coli strains. The toxin recognizes sialoglycans for entry and cleaves an endoplasmic reticulum chaperon, binding immunoglobulin protein, to cause cell death. However, no systematic screening has yet been performed to identify critical host factors. Here, we performed a genome-wide CRISPR/Cas9 knockout screen for SubAB-induced cell death and identified various sialoglycan-related and membrane-trafficking genes. Analysis of glycan-deficient cells demonstrated that not only N-glycans but also O-glycans serve as SubAB receptors. In addition, SLC39A9, which is a predicted zinc transporter, as well as KDELRs and JTB, were required for SubAB to induce maximal cell death. Disruption of the SLC39A9 gene markedly reduced both complex-type N-glycans and core 1 O-glycans, and the O-glycan reduction was attributed to the reduction of core 1 synthase (C1GalT1). These results provide insights into the post-transcriptional regulation of glycosyltransferases by SLC39A9, as well as sialoglycan species as SubAB receptors. [Display omitted] •CRISPR knockout screening identified host factors for SubAB-induced cell death•O-glycans as well as N-glycans serve as SubAB receptors•Loss of SLC39A9 as well as loss of KDELR2 and JTB reduces sensitivity to SubAB•SLC39A9 is required for biosynthesis of complex-type N-glycans and core 1 O-glycans Biological Sciences; Biochemistry; Molecular Biology; Microbiology; Cell Biology